Electronic band structure modulated by local surface strain in the (111) facet of the 〈112〉 silicon nanowires. (April 2015) - Zhang, Lihong; Xin, Xiaojun; Guo, Chunsheng; Gan, Liyong; Zhao, Yong
Abstract: Based on the models built with our "cyclic replacement" method we introduced local strain into the (111) facet of the Si 〈112〉 nanowires. With ab initio approach, it is found that the electronic band structures of the nanowires are modulated efficiently by the surface strains: the indirect band gap declines by strong surface compression, while it always decreases and impressively changes to a direct band gap with surface tension. Moreover, the local deformations result in spatial separation of the valence band minimum to the compressed surface and the conduction band minimum to the tensed surface. highlights: We introduce surface deformationinto a surface. We examine the electronic band gap modulated by surface deformations. Indirect-to-direct band gap transition occurs due to the surface tensile strain. Spatial separation of valence band minimum and conduction band minimum of the Si nanowires occurs due to surface strain.